2006
DOI: 10.1186/1471-2458-6-216
|View full text |Cite
|
Sign up to set email alerts
|

Patients in long-term maintenance therapy for drug use in Italy: analysis of some parameters of social integration and serological status for infectious diseases in a cohort of 1091 patients

Abstract: Background: Heroin addiction often severely disrupts normal social functioning. The aims of this multi-centre study of heroin users in long-term replacement treatment were: i) to provide information on aspects of social condition such as employment, educational background, living status, partner status and any history of drug addiction for partners, comparing these data with that of the general population; ii) to assess the prevalence of hepatitis, syphilis and HIV, because serological status could be a reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
2
9
0
1
Order By: Relevance
“…In 2006, 10,000 opiate-dependant patients received treatment for addiction in over 500 SerTs nationwide. Both methadone and buprenorphine are approved drugs for pharmacotherapy of addiction, although methadone is prescribed in over 80% of cases [11], and each regional government oversees policy on dispensation and dosing schedules. Few studies have investigated the efficacy of regional SerTs regarding retention in treatment and relapse to drug use; however, a recent survey of 115 SerTs reported that in 80% of clinics, the average dose of methadone for maintenance treatment was < 60 mg/day, lower than that recommended by international guidelines.…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…In 2006, 10,000 opiate-dependant patients received treatment for addiction in over 500 SerTs nationwide. Both methadone and buprenorphine are approved drugs for pharmacotherapy of addiction, although methadone is prescribed in over 80% of cases [11], and each regional government oversees policy on dispensation and dosing schedules. Few studies have investigated the efficacy of regional SerTs regarding retention in treatment and relapse to drug use; however, a recent survey of 115 SerTs reported that in 80% of clinics, the average dose of methadone for maintenance treatment was < 60 mg/day, lower than that recommended by international guidelines.…”
Section: Commentarymentioning
confidence: 99%
“…[5,11] There is convincing evidence provided by Sylvestre and colleagues that when antiviral treatment is managed in cooperation with the staff of a methadone (or buprenorphine) maintenance program, compliance is maximized and outcome is comparable to that of non-opiate-maintained HCV patients. [14]…”
Section: Commentarymentioning
confidence: 99%
“…In Europe, from 20% to 60% of IDUs are seropositive for HBV. The prevalence of HBV infection among DUs attending a methadone maintenance treatment (MMT) in Geneva was much greater among older DUs (80.5%) than younger ones (20.1%) [ 5 , 28 , 29 ]. The seroconversion rate for HBV in a cohort of IDUs enrolled in a syringe exchange program in Malmo was 11.7% per year (compare with no seroconversion among those with HIV) [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…16 PCDUs provide a comprehensive range of services: counseling, treatment for drug withdrawal, short-term detoxification, agonist maintenance treatment, selection for therapeutic communities, psychotherapy, antihepatitis vaccination, and laboratory testing among other services. Most of the patients in PCDUs are seeking treatment for heroin dependence, although the PCDUs also provide services for cocaine dependence and alcohol dependence.…”
mentioning
confidence: 99%